Stages and peculiarities of legal recognition of the fight of the UPA for an independent Ukraine in national legislation (in the honor of the 80th anniversary of the Ukrainian Insurgent Army`s formation) - Ukhach, Vasyl (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
During the Soviet totalitarian regime, an objective historical and legal assessment of the struggle of the Organization of Ukrainian Nationalists and the Ukrainian Insurgent Army was impossible. Communist propaganda, grossly violating the norms of the international humanitarian law, purposefully declared the fighters for the freedom of Ukraine as "bandits" turning them from the combatants into the criminals.The aim of the research is to distinguish the stages and highlight the process of legal recognition of the UPA's armed struggle for an independent cathedral Ukrainian state in Ukrainian legislation. The following research tasks were set: 1) to reveal the attempts of public organizations, state authorities, and scientific institutes in the first years of independence, to draw the conclusions regarding the historical and legal assessment of the struggle of the OUN and the UPA; 2) carry out an analysis of the development of the national legislation due to the assessment of subjects of the Ukrainian liberation movement of the 30s-50s of the 20th century in the period from 1997 to 2014; 3) reveal the process of the recognition of the UPA army and its soldiers as fighters for independence after the Revolution of Dignity.The process of rehabilitation and objective historical and legal qualification of the UPA's activities was not easy and progress directly proportionally depended on the dominance of pro-Ukrainian parties in the parliament and the Ukrainian-centric discourse in the society in this matter. According to the Law of Ukraine "On the Legal Status and Honoring the Memory of Fighters for Ukraine`s Independence in the 20th Century" (2015), the UPA appeared as a national liberation army that fought for the Ukrainian independent cathedral state, and its soldiers were fighters for the independence of Ukraine in the 20th century. A positive consequence of the adoption of the Law should be a significant reduction of social and political tension regarding the social and historical and legal assessment of the national liberation struggle in the 20th century, especially in the conditions of the aggression of the russian federation against Ukraine, which will form a true picture of the public vision of the processes of Ukrainian state-building.